Surgical management of abnormally invasive placenta: a retrospective cohort study demonstrating the benefits of a standardized operative approach. (15th October 2015) - Brennan, Donal J.; Schulze, Brittany; Chetty, Naven; Crandon, Alex; Petersen, Scott G.; Gardener, Glenn; Perrin, Lewis
Abstract: Introduction: Abnormally invasive placenta is a major cause of maternal morbidity and mortality. The aim of this study was to assess the effectiveness of a standardized operative approach performed by gynecological oncologists in the surgical management of abnormally invasive placenta. Materials and methods: We performed a retrospective analysis of all cases of morbid placental adherence managed at the Mater Mothers' Hospitals, Brisbane, Australia between January 2000 and June 2013. A standard operative approach involving extensive retro‐peritoneal and bladder dissection before delivery of the fetus, was undertaken when a gynecological oncologist was present at the start of the procedure. Main outcome measures were estimated blood loss, transfusion requirements, and maternal and neonatal morbidity. Results: The study includes 98 cases of histologically confirmed abnormally invasive placenta. Median estimated blood loss for the entire cohort was 2150 mL (range 300–11 500 mL). Women were divided into three groups, (1) those who had a gynecological oncologist present at the start of the procedure (group 1; n = 43), (2) those who had a gynecological oncologist called in during the procedure (group 2; n = 23), and (3) those who had no gynecological oncologist involved (group 3; n = 32). Group 2 had a significantly higher blood loss than the other groups ( p = 0.001) (median 4400 mL). Transfusion requirements were higher in groups 2 and 3 compared with group 1 ( p = 0.004). Other maternal and neonatal morbidity was similar across all three groups. Conclusion: This study supports the early presence of a gynecological oncologist at delivery when abnormally invasive placenta is suspected and demonstrates that a "call if needed" approach is not acceptable for these complex cases.